(untitled) (Journal of Hama University, 2021)
Background: Hospital nursing staff constitute the largest proportion of health workers, and they provide services and activities of a special nature and specific goals derived from the general objectives of the hospital, Where the head nurse is responsible for managing nursing services, and she is charged with directing nurses and supervising their activities, and controlling is one of the most important measures taken by the institution in facing risks and limiting them and reducing the percentage of errors and deviations to the minimum possible. Aim: the aim of this study was to evaluate the controlling role of the head nurses. Methods: The descriptive analytical approach was followed, and the research sample consisted of all head nurses, who numbered (43) at Tishreen University Hospital, the data were collected using a cognitive test for the head nurses’ information in control and a check list to note their supervisory behavior by the researcher. Results: The results showed that most of the heads nurses didn’t apply the control behaviors related to following the relationship of the nursing staff with each other, explaining or recalling the main goal of the control process, following up the relationship of the nursing staff with patients and asking the patients about their satisfaction or having problems with the nursing staff, and holding daily meetings. This may indicate the weak communication skills of the heads of the nursing divisions on the one hand, and their weak role in managing the nursing division on the other hand. Conclusion and Recommendations: The study recommended to develop an advanced and modern controlling system to control the administrative behavior of the practices of the nursing staff and the head nurses, so that this system contains performance standards and tools for administrative control, and this system writes reports that reveal all kinds of violations and deviations in performance.